Effect of a hearing loss care education program for older adults targeted at visiting nurses: A cluster randomized controlled trial - Sumiyo Nabeshima; Saiko Sugiura; Kiyomi Yamada; Sayuri Sable-Morita; Yukako Ando (PLoS ONE, 2026)
Hearing loss in older adults is a risk factor for depression, cognitive decline, frailty, and other conditions, and it has various negative physical and psychological effects. Hearing loss care requires the support of medical professionals; however, most hearing care education is targeted at professionals working in hospitals and care facilities, with few interventions aimed at visiting nurses. To address this gap, we developed the “Hearing Loss Care Education Program for the Older Adults” to improve visiting nurses’ skills in managing hearing loss. This study aimed to evaluate the effectiveness of the program. This cluster randomized controlled trial was registered in the UMIN Clinical Trials Registry (UMIN000053337) and conducted across 22 visiting nursing stations: 11 in the intervention group (60 visiting nurses) and 11 in the control group (42 visiting nurses). The intervention consisted of on-demand lectures and technical exercises, followed by a 3-month follow-up period. The primary outcome was the “implementation of hearing care,” whereas the secondary outcomes were “knowledge of hearing care” and “confidence in implementing hearing care.” Between-group differences were analyzed using generalized estimating equations. As part of the primary outcome, a significant increase in the implementation of “hearing screening” was observed in the intervention group (odds ratio 8.35, 95% confidence interval 3.60–19.34, p < 0.001). Additionally, the intervention group demonstrated significantly higher “knowledge of hearing care” and “confidence in implementing hearing care.” These findings suggest that the program effectively enhanced visiting nurses’ knowledge and confidence in hearing care and supports the integration of hearing screening into their routine practice.